Popularização da ciência: um olhar para o ensino linguístico e literário - Favaretto, Lucas Martins (2024)
This research investigates the relationship between the popularization of science and the teaching of language and literature, focusing on how language facilitates access to scientific knowledge among the population. The study is structured into six sections, exploring the definition of science popularization, linguistic science, literary science, the relationship between the two, and their role in the curriculum of a Languages program, as well as the research’s conclusions. In addition to discussing the central concept, the paper also addresses vulgarization, diffusion, and scientific literacy as areas for further exploration. The text emphasizes interdisciplinarity, linking the areas discussed through a theoretical framework that includes works by Marcelo Gomes Germano (2011), Alzira Lobo de Arruda Campos (2004) and Antonio Cândido (2006). The focus of the analysis is on how science can be popularized to various audiences outside the academic environment.